Cutaneous metastases of papillary renal cell carcinoma: A case report and review of the literature. (13th August 2019) - Cardwell, Leah A.; Bender, Nicole R.; Sokumbi, Olayemi
Abstract: Papillary renal cell carcinoma (RCC) is an uncommon subtype of RCC that is typically encountered at early stages and has a high survival rate. Histopathology typically shows well‐defined papillary architecture with tumor cells lining fibrovascular cores and can be further subdivided into type 1 and type 2 tumors based on cytology and genetic basis. Type 1 tumors have a single layer of basophilic cells and low nuclear atypia, while type 2 tumors have a pseudostratified layer of eosinophilic cells and high nuclear atypia. Some tumors have overlapping features of both types. We present a unique case of cutaneous metastases of papillary RCC with typical papillary architecture in the dermis and review the literature on this rare entity.